Strategi Perencanaan Pembangunan Berkelanjutan - Anggi Maharani Nasution; Nadia Ulfa; Nurhayati Harahap (Universitas 45 Surabaya, 2024)
Strategic planning for sustainable development is a plan that is developed to ensure that development can take place in a sustainable manner, where The requirements of today's population can be fulfilled without jeopardizing the necessities of generations to come. Strategic planning for organizations and the business world is a solution to all the problems that arise when designing long-term plans. In this case, it is expected that leaders have the ability to plan by considering the problems, obstacles, and challenges faced by the organization, so that they can make strategic decisions. Formulate tactical plans that align with the requirements of the organization.In other words, strategic planning is required when designing programs that focus on sustainable development. Therefore, an understanding of the elements required for sustainable development, including the necessary factors and tools, at both national and local levels, is essential. This article is a review that discusses various aspects of strategic planning and sustainable development, as well as the process of preparing it, and the advantages that can be obtained through an organization or business.